2021
DOI: 10.1186/s12885-021-08954-7
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β protects osteosarcoma cells from chemotherapeutic cytotoxicity in a SDH/HIF1α dependent manner

Abstract: Background In the widespread adoption of chemotherapy, drug resistance has been the major obstacle to tumor elimination in cancer patients. Our aim was to explore the role of TGF-β in osteosarcoma-associated chemoresistance. Methods We performed a cytotoxicity analysis of methotrexate (MTX) and cisplatin (CIS) in TGF-β-treated osteosarcoma cells. Then, the metabolite profile of the core metabolic energy pathways in Saos-2 and MG-63 cell extracts wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
(38 reference statements)
1
8
0
Order By: Relevance
“…Circ‐ECE1, Her4, and PDGFRβ increase glucose uptake and promote metabolic reprogramming in OS through cMyc 24–26 . MiR‐186, KRT17 and TGF‐β promote glucose uptake and glycolysis in OS cells via HIF‐1ɑ 27–29 . The miR‐200c plays a central role in glucose metabolism in cancer cells, and CircCSPP1 may influence miR‐200c maturation to regulate glucose uptake and cell proliferation to promote OS 30 .…”
Section: Glycolysis In Osteosarcomamentioning
confidence: 99%
See 2 more Smart Citations
“…Circ‐ECE1, Her4, and PDGFRβ increase glucose uptake and promote metabolic reprogramming in OS through cMyc 24–26 . MiR‐186, KRT17 and TGF‐β promote glucose uptake and glycolysis in OS cells via HIF‐1ɑ 27–29 . The miR‐200c plays a central role in glucose metabolism in cancer cells, and CircCSPP1 may influence miR‐200c maturation to regulate glucose uptake and cell proliferation to promote OS 30 .…”
Section: Glycolysis In Osteosarcomamentioning
confidence: 99%
“…Xu et al. found that reduced SDH expression in OS cells led to an accumulation of succinate, and TGF‐β reduced SDH expression by decreasing STAT1, leading to upregulation of HIF1α, which alters glucose metabolism and exacerbates chemoresistance in OS cells 29 . Ziemann and colleagues discovered that MiR‐101‐3p was a tumor suppressor that regulates mitochondrial metabolism of OS cells by regulating mtDNA transcription and complex II 128 …”
Section: The Tricarboxylic Acid Cycle In Osteosarcoma Mitochondriamentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation of glycolysis by TGF-β has also been reported in OS. TGF-β weakens succinate dehydrogenase (SDH) expression by reducing the transcription factor STAT1, which leads to the accumulation of succinate and the increase of HIF-1α in OS cells, then changes the glycolysis state and drug resistance of OS cells ( Xu et al, 2021 ). Moreover, TGF-β inhibitor RepSox inhibits OS proliferation and EMT and promotes apoptosis by inhibiting the JNK/Smad3 signal pathway ( He et al, 2021 ).…”
Section: The Glycolysis In Osteosarcomamentioning
confidence: 99%
“…TGF-β negative transcription factor STAT1 further inhibited the expression of succinate dehydrogenase (SDH). The decrease of SDH leads to HIF-1α upregulation, which changes the metabolic level of glucose and the drug resistance of OS cells ( Xu et al, 2021 ). The miR-186 inhibits the proliferation, invasion, and glycolysis of OS cells by targeting HIF-1α and pituitary tumor transforming gene 1 (PTTG1) ( Xiao et al, 2018 ).…”
Section: The Glycolysis In Osteosarcomamentioning
confidence: 99%